Pour un projet de développement territorial associé au RER bruxellois - Patrick Frenay (Brussels Studies)
This contribution first attempts to discuss the challenges of railway development which lie behind the RER project in and around Brussels.It then proposes conceptual approaches for the optimal implementation of this project, brought into line with the other components of the rail service (in particular the HST and IC/IR services).It also attempts to decipher the challenges in terms of the positioning of opposed institutional stakeholders, emphasising the objective competition which motivates them and the relatively isolated position of the Brussels-Capital Region which, according to the author, results from this.Finally, the author proposes approaches to a “railway strategy” in Brussels, aimed in particular at supporting a different type of territorial development from that which prevails in the current Regional Development Plan, i.e. to favour a multipolar city, targeted spatially.